2009
DOI: 10.1515/bc.2009.091
|View full text |Cite
|
Sign up to set email alerts
|

The nanodisc: a novel tool for membrane protein studies

Abstract: A major challenge in the research on membrane-anchored and integral membrane protein complexes is to obtain these in a functionally active, water-soluble, and monodisperse form. This requires the incorporation of the membrane proteins into a native-like membrane or detergent micelle that mimics the properties of the original biological membrane. However, solubilization in detergents or reconstitution in liposomes or supported monolayers sometimes suffers from loss of activity and problematic analyses due to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 79 publications
(115 reference statements)
0
121
0
Order By: Relevance
“…However, these preparations represent an over-simplified system in a non-native environment. To overcome these problems, several approaches have been put forward: (i) reducing the number of components involved in NPQ in the thylakoid membrane by using mutants lacking photosystems I and II core complexes or blocking the chloroplast translation that leads to membranes enriched in LHCII (15,16) and (ii) studying isolated LHCII in detergent-free environment using nanodisks (17), styrene maleic acid (18), amphipoles (19), or liposomes (20 -22). These methods have revealed that the lifetime of LHCII in the membrane differs substantially from its lifetime in detergent micelles, suggesting that in the natural environment the antennas assume a different and more quenched conformation.…”
mentioning
confidence: 99%
“…However, these preparations represent an over-simplified system in a non-native environment. To overcome these problems, several approaches have been put forward: (i) reducing the number of components involved in NPQ in the thylakoid membrane by using mutants lacking photosystems I and II core complexes or blocking the chloroplast translation that leads to membranes enriched in LHCII (15,16) and (ii) studying isolated LHCII in detergent-free environment using nanodisks (17), styrene maleic acid (18), amphipoles (19), or liposomes (20 -22). These methods have revealed that the lifetime of LHCII in the membrane differs substantially from its lifetime in detergent micelles, suggesting that in the natural environment the antennas assume a different and more quenched conformation.…”
mentioning
confidence: 99%
“…These constructs maintain a very well-defined size depending on the type of protein coat [67] . Because the smallest nanodiscs are approximately 10 nm, their application in crystallography is still quite limited, and more work needs to be performed to remove the 3-D packing restraints before successful crystallization.…”
Section: Bicelle Methodsmentioning
confidence: 99%
“…Because the smallest nanodiscs are approximately 10 nm, their application in crystallography is still quite limited, and more work needs to be performed to remove the 3-D packing restraints before successful crystallization. To date, these bilayer-based, diffusible structures have been most useful for NMR methods or for assessing the ligand binding of GPCRs [67][68][69] .…”
Section: Bicelle Methodsmentioning
confidence: 99%
“…Nanodiscs are similar to high-density lipoprotein particles and consist of fairly large patches of planar lipid bilayers (~160 lipid molecules) surrounded by the rim formed by apolipoprotein A-I (Borch & Hamann, 2009;Nath et al, 2007;Ritchie et al, 2007). The particles have the diameter of about 12 nm and thickness of 4 nm with the overall rotational correlation time of about 80 ns (Lyukmanova et a., 2008), which is rather high for structural NMR studies, but with TROSY (Pervushin et al, 1997) and CRINEPT (Riek et al, 1999) techniques one can record a readable heteronuclear spectrum and compare it to the one recorded in micelles or bicelles.…”
Section: Determination Of High-resolution Structure Of Dimeric Transmmentioning
confidence: 99%
“…Nanodiscs have only been applied in NMR spectroscopy for a couple of years and but few membrane protein were studied in this environment so far. However, they proved useful for verifying that other membrane mimicking media provide proper tertiary structure of membrane proteins (Shenkarev et al, 2010); they also have high potential for various bioassay applications (Borch & Hamann, 2009).…”
Section: Determination Of High-resolution Structure Of Dimeric Transmmentioning
confidence: 99%